Macrophage‐mediated extracellular matrix remodeling after fat grafting in nude mice. Issue 10 (13th September 2022) - Zhang, Xiangdong; Jin, Xiaoxuan; Li, Yibao; Xu, Mimi; Yao, Yao; Liu, Kaiyang; Ma, Chijuan; Zhang, Yuchen; Ru, Jiangjiang; He, Yunfan; Gao, Jianhua
Abstract: Clinical unpredictability and variability following fat grafting remain non‐negligible problems due to the unknown mechanism of grafted fat retention. The role of the extracellular matrix (ECM), which renders cells with structural and biochemical support, has been ignored. This study aimed to clarify the ECM remodeling process, related cellular events, and the spatiotemporal relationship between ECM remodeling and adipocyte survival and adipogenesis after fat grafting. Labeled Coleman fat by the matrix‐tracing technique was grafted in nude mice. The ECM remodeling process and cellular events were assessed in vivo. The related cytokines were evaluated by qRT‐PCR. An in vitro cell migration assay was performed to verify the chemotactic effect of M2‐like macrophages on fibroblasts. The results demonstrated that in the periphery, most of the adipocytes of the graft survived or regenerated, and the graft‐derived ECM was gradually replaced by the newly‐formed ECM. In the central parts, most adipocytes in the grafts died shortly after, and a small part of the graft‐derived and newly‐formed ECM was expressed with irregular morphology. Adipose ECM remodeling is associated with increased infiltration of macrophages and fibroblasts, as well as up‐regulated expression of cytokines in the adipose tissue. To sum up, our results describe the various preservation mode of fat grafts after transplantation and underscore the importance of macrophage‐mediated ECM remodeling in graft preservation after fat grafting. The appreciation and manipulation of underlying mechanisms that are operant in this setting stand to explore new therapeutic approaches and improve clinical outcomes of fat grafting.